Design and tuning of a fuzzy proportional retarded controller: frequency approach - R. Villafuerte; J.A. Ortega Melo (Revista Iberoamericana de Automática e Informática Industrial RIAI)
The time delays are usually an undesirable phenomenon in the control processes, because these can induce instability or a poor performance in the system. However, the time delays have the property of assisting in stabilizing. This article benefiting from this property to propose the design and tuning of a fuzzy proportional retarded controller (BPR) to stabilize a class of nonlinear systems. In this frame, the stabilization of a nonlinear system is guaranteed through the σ-stability of its Takagi-Sugeno (TS) fuzzy model in close-loop with BPR controller. The BPR controller design is based on inclusion a retarded action in the conventional structure. While the tuning of the BPR control law, has been addressed in the frequency approach using D-partition method. The stability of TS-BPR fuzzy system is ensured by analazing the root locus of its characteristic quasipolynomial. The design and tuning of BPR controller are exemplified on a car-pendulum experimental platform. The performance of BPR is compared with a parallel distributed compensation classic.